CHARACTERISTICS AND RISK FACTORS OF YOUNG ATHEROSCLEROTIC CARDIOVASCULAR DISEASE IN AN UNDERREPRESENTED COHORT: INSIGHTS FROM THE ALL OF US RESEARCH PROGRAM - Sara J. King, MD (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Recent research has found an increasing prevalence of atherosclerotic cardiovascular disease (ASCVD) in young adults (ages less than 50), however most studies were performed in predominantly White populations. We sought to evaluate the demographics, traditional medical risk factors, and social determinants of health of young ASCVD in the All of Us Research Program, an emerging national cohort study that seeks to investigate underrepresented populations. Methods: We queried the All of Us database for individuals ages 20 to 49 years from 2017 to March, 2024 with completed data on demographics, income, education, and insurance. ASCVD was defined using ICD-10 codes for coronary artery disease (I20-I25) and stroke (I63, I65). Traditional medical risk factors were defined using ICD-10 codes and included type 2 diabetes mellitus (T2DM), hypertension, and hyperlipidemia. Tobacco use and obesity were defined using survey responses and body mass index, respectively. Unadjusted univariate and adjusted multivariate logistic regression models were performed with ASCVD as outcome and reported as odds ratios (OR) with 95% confidence intervals (CI). Results: There were 90,313 individuals included, with 64.3% female, 50.2% non-white race, 24.5% Hispanic or Latino or other ethnicity, and 58.4% with annual income under $50,000. ASCVD was present in 2,219 (2.5%). In unadjusted univariate models, age (OR 1.10, CI 1.09-1.11), male gender (OR 1.16, CI 1.06-1.27), Black race (OR 1.46, CI 1.32-1.62), other race (OR 1.17, CI 1.04-1.30), annual incomes less than $25,000 (ORs 1.26-1.77, CIs 1.04-2.22), and traditional medical risk factors were associated with ASCVD. In adjusted multivariate logistic regression models, age, male gender, Black race, annual incomes less than $25,000, most education levels lower than college graduate, and traditional medical risk factors except obesity were associated with ASCVD, with hypertension showing the strongest association (Figure 1). Having medical insurance was associated with higher odds of ASCVD. Conclusions: Several traditionally underrepresented groups including Black race, low annual income (less than $25,000), and education levels lower than college graduate were associated with ASCVD at a young age.